2019
DOI: 10.1016/j.bjorl.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of tonsillectomy efficacy in children with PFAPA syndrome

Abstract: Tonsillectomy is a good option for the treatment of PFAPA syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The long‐term prognosis of PFAPA after tonsillectomy is good. A prospective Turkish series of 23 PFAPA patients reported sustained remission after tonsillectomy in 91% of cases in a one‐year follow‐up . Licameli et al.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The long‐term prognosis of PFAPA after tonsillectomy is good. A prospective Turkish series of 23 PFAPA patients reported sustained remission after tonsillectomy in 91% of cases in a one‐year follow‐up . Licameli et al.…”
Section: Resultsmentioning
confidence: 93%
“…The most distinctive feature of PFAPA is a clockwork periodicity of fevers . In most cases, the episodes can be forecasted within a margin of seven days .…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study of 23 patients, 91% of patients had complete resolution of PFAPA symptoms immediately after surgery, with 100% of patients achieving resolution within 3 months [48]. Finally, a Cochrane review of randomized controlled trials (n = 65) comparing surgery versus corticosteroids or expectant management found complete resolution in all tonsillectomy patients by the end of 6 months [37]. In this study of 87 patients, there was a 73.1% success rate of tonsillectomies resolving episodes, which correlates well with previous literature results.…”
Section: Resultsmentioning
confidence: 98%
“…Tonsillectomy has been shown to be helpful. In a recent Cochrane review, there was a relative risk reduction of 4.38 in PFAPA symptoms and an overall reduction in both severity and frequency of episodes post-tonsillectomy [37]. Demonstrating a possible link between FMF and PFAPA, colchicine, an anti-inflammatory medication commonly used in the treatment of FMF, has been shown to increase the interval between episodes but does not reduce the severity and has been reserved for patients whose symptoms do not resolve following tonsillectomy [35].…”
Section: Research Articlementioning
confidence: 99%
“…Moreover, after their use interval between flares can become shorter. Tonsillectomy also demonstrated a good result in the majority of cases [16]. If flare episodes are frequent and / or tonsillectomy is ineffective, colchicine may be used to increase the interval between episodes [17].…”
Section: Introductionmentioning
confidence: 95%